2008
DOI: 10.1016/j.crohns.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ulcerative colitis and Crohn's disease in Danish children: Still rising or levelling out?

Abstract: In our study we found an insignificant increase in the incidence of both CD and UC, indicating that the previously reported rising incidence might be levelling out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
4
18
2
Order By: Relevance
“…DTPM measures local perfusion whereas the indices refer to indirect criteria only. Similar results were found by others comparing bowel wall thickening and biochemical indices of inflammation (Mayer et al, 2000) 3.1.2 Ulcerative colitis (UC) As in CrD UC-incidence is increasing too (Jakobsen et al, 2008) but contradictory reports have been also published (Loftus et al, 2007;Molinie et al, 2004). In less industrialized regions similar incidences as in industrialized countries were found for both CD and UC (Sood et al, 2003).…”
Section: Crohn Disease (Crd)supporting
confidence: 76%
“…DTPM measures local perfusion whereas the indices refer to indirect criteria only. Similar results were found by others comparing bowel wall thickening and biochemical indices of inflammation (Mayer et al, 2000) 3.1.2 Ulcerative colitis (UC) As in CrD UC-incidence is increasing too (Jakobsen et al, 2008) but contradictory reports have been also published (Loftus et al, 2007;Molinie et al, 2004). In less industrialized regions similar incidences as in industrialized countries were found for both CD and UC (Sood et al, 2003).…”
Section: Crohn Disease (Crd)supporting
confidence: 76%
“…This has previously been demonstrated in several studies [1,3,9,[23][24][25][26]. A recent study from eastern Denmark [27] covering 43% of the Danish population below 15 years of age indicated that the increasing tendency for CD could be levelling out. The major increase in CD incidence occurred in the late 1980s and the 1990s in Scandinavia, whereas the increase seemed to have occurred earlier in Scotland [1,28].…”
Section: Discussionmentioning
confidence: 72%
“…5,24,30 However, other studies reported that rates plateau rather than significantly change. 7,31 In view of the fact that the population of Saudi Arabia is stable, the significantly increased incidence over time points to a major role of the environment. The discovery of oil in the KSA several decades ago led to rapid changes in all aspects of life.…”
Section: Discussionmentioning
confidence: 97%
“…4 In addition to this high baseline incidence in the West, a trend of increasing IBD incidence over time has been reported in many countries, 5,6 whereas data from other Western countries suggest that the incidence may be reaching a plateau. 7 Pediatric IBD has been reported from non-Western countries, such as Kuwait, 8 Thailand, 9 Mexico, 10 Libya, 11 Taiwan, 12 Iran, 13 India, 14 and China. 15 In the Kingdom of Saudi Arabia (KSA), IBD, which was rarely diagnosed several decades ago, is increasingly reported in both adults and children.…”
mentioning
confidence: 98%